Role of open cerclage wiring in patients with comminuted fractures of the femoral shaft treated with intramedullary nails - Tzu-Hao Wang; Hao-Chun Chuang; Fa-Chuan Kuan; Chih-Kai Hong; Ming-Long Yeh; Wei-Ren Su; Kai-Lan Hsu (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Introduction The role of open cerclage wiring in comminuted femoral shaft fracture treatment with intramedullary nails remains unclear. Here, we analyzed the effect of open cerclage wiring and the risk factors for nonunion after interlocking nailing in comminuted femoral shaft fracture treatment. We hypothesized that open cerclage wiring can be applied in patients with severe comminuted femoral shaft fractures without affecting bone healing. Patients and methods This retrospective cohort study used data from consecutive patients who underwent interlocking nail fixation of a comminuted femoral shaft fracture between January 1, 2009, and December 31, 2016. First, eligible patients were divided into the wire and no wire groups according to the surgical technique used, and their union rate was recorded. The patients were then divided into the union and nonunion groups, and their perioperative data were analyzed. Results In total, 71 comminuted femoral shaft fractures treated with interlocking nail fixation were included: 38 fractures (53.5%) augmented with the open wiring technique and 33 reduced with closed or mini-open techniques without wiring. The wire group demonstrated significant improvements in fracture reduction compared with the no wire group, whereas no significant difference was observed in the union rate between the wire and no wire groups (p = 0.180). Moreover, 46 (65%) of 71 fractures achieved union smoothly, and no significant difference was observed in any perioperative data between the union and nonunion groups. Discussion Augmentation with open cerclage wiring is indicated for comminuted femoral shaft fractures treated with intramedullary nails, even when the fragments are large or greatly displaced. Thus, open cerclage wiring can be used for fracture treatment without decreasing the union rate.